Computational Study of Transient Conjugate Conductive Heat Transfer in Light Porous Building Walls [Estudio Computacional Transiente de Conducción Conjugada en Paredes de Materiales Porosos Ligeros] - Saavedra-Flores, E; Diaz-Matus, A; Baez-Vargas, S; Vasco-Calle, D (Universidad de Tarapaca, 2017)
The present work was originally carried out as a project by HVAC-R engineering students of a heat transfer undergraduate course. The main goal was to introduce to the students to the implementation of a commercial simulation tool, ANSYS/Transient thermal, to analyze a transient heat transfer process of their professional interest. Behind this goal there were a set of activities that lead students to learn very important lessons that deal with computational simulation: physical and mathematical modeling, validation, measurement of thermal properties and grid size analysis. Specifically, a computational simulation of the transient cooling process of two composed building walls initially at 20 °C was performed. Boundary conditions of third kind were imposed at the outer surfaces of the walls. The composed walls are made of light materials: oriented strand board and plasterboard, which are porous building materials and whose thermal properties can be improved by imbibe them with phase change materials (PCM). The convective heat transfer coefficients were taken from the Chilean normative (Nch853-Of91) and some of the thermophysical properties were experimentally obtained. © 2017, Universidad de Tarapaca. All rights reserved.